Inventory of Mammal Species Using Camera Trap in Pondok Parian Nagari Forest, Lunang, Pesisir Selatan Regency, West Sumatra - Tassya Putri; Reki Kardiman; Fitra Nugraha (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Mammal inventory is a survey activity to find mammal species that exist in a certain area at a certain time and point. The existence of mammals in a forest area helps restore forest conditions through their role as natural predators and seeds dispersing. Nagari Forest is one of the efforts to maintain the existence of forests and biodiversity that have ecological, economic, socials and cultural benefits. The aim of this study was to determine the types of mammals found in Pondok Parian Nagari Forest, Lunang based on the results of camera trap recordings. This research is descriptive study, conducted from July 2022 to January 2023. Located in Pondok Parian Nagari Forest, Lunang, West Sumatra. Data collection using the camera trap method. The data obtained was analyzed and then arranged into the table consisting of orders, famili and species. The camera trap succeeded in documenting 19 species of mammals belonging to 14 families and 6 orders. Those identified species were Tapirus indicus, Capricornis sumatraensis, Muntiacus muntjac, Tragulus napu, Cuon alpinus, Neofelis diardi, Prionailurus bengalensis, Pardofelis marmorata, Helarctos malayanus, Martes flavigula, Hemigalus derbyanus, Paguma larvata, Viverra tangalunga, Arctictis binturong, Hystrix brachyura, Macaca namestrina, Presbytis melalophos, Macaca fascicularis, Echinosorex gymnure.